Педагогічні умови підвищення ефективності громадянського виховання дітей дошкільного віку - Кузава, Ірина; Ланевич, Наталія (My University, 2018)
У статті науково обґрунтовано й проаналізовано педагогічні умови підвищення ефективності громадянського виховання дітей дошкільного віку. Встановлено, що виховання громадянина демократичного суспільства вимагає створення педагогічних умов, які б сприяли розвитку громадянських якостей дошкільників, а саме: використання народної творчості, традицій українського народу; наповнення змісту навчального матеріалу громадянським компонентом; підвищення професійної компетентності педагогів дошкільної освіти з питань громадянського виховання; гуманізація і демократизація педагогічної взаємодії, спрямована на забезпечення позитивного емоційного стану дітей; індивідуальний підхід, який передбачає вміння педагога бачити у кожній дитині особистість, визнавати за нею право на власні погляди, захоплення, інтереси.In the article the pedagogical conditions for increasing the efficiency of civic education of preschool children are scientifically substantiated and analyzed. The national revival of Ukraine sharply raises the problem of civic education of the individual. Of great importance in the system of work of pre-school educational institutions acquire historical-cultural, labor, moral and ethical, natural values that contain the environment of the region, A conscious support to the progressive traditions of folk pedagogy, the legacy of outstanding teachers, and the modern conceptual foundations of civic education in Ukraine. The construction of a new civil, democratic, humane, and legal society focused on high national and universal values, becomes relevant in the strategy of modern Ukrainian education. In view of this, the need to introduce a holistic system of civic education into the educational process of pre-school establishments becomes a necessary factor in modern educational reform. As a result of the theoretical analysis of scientific sources, it is confirmed that one of the most pressing problems of pedagogical theory and practice is the search for new forms and methods of civic upbringing of preschool children that would meet modern social needs. In this regard, traditional and interactive forms and methods are defined and classified, which, based on a democratic style of interaction, aim at creating critical thinking, initiative, and creative activity in children. It was established that the education of a citizen of a democratic society requires the creation of pedagogical conditions that would promote the development of the civic qualities of junior pupils, namely: use of folk art, traditions of the Ukrainian people; filling the content of the educational material with the civil component; raising the professional competence of primary education teachers in the field of civic upbringing of preschoolers; humanization and democratization of pedagogical interaction, aimed at providing a positive emotional state of children; an individual approach that involves the teacher's ability to see each child's personality, to recognize her right to her own views, hobbies, interests. In the course of the study it was determined that the prognosis of the results of educational influence, ie, the civic education of preschool children, is an important condition for the effectiveness of civic education.
Keywords: педагогічні умови; громадянське виховання; громадянськість; діти дошкільного віку